2018
DOI: 10.1108/imds-10-2017-0486
|View full text |Cite
|
Sign up to set email alerts
|

Physical-internet-enabled auction logistics in perishable supply chain trading

Abstract: Purpose While significant efforts have been made to study auction and logistics theories in the context of perishable supply chain trading (PSCT) over the last few years, the consensus has not yet been reached on how best to examine the impact of physical-internet-enabled auction logistics (AL) decisions and processes on dynamic perishable products transactions. The purpose of this paper is to address this gap by investigating the existing situations and identifying future opportunities for both academic and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…By promoting the creation of delivery channels (Luo et al, 2021), PI aims to reduce the fragmentation of logistics services by sharing logistics assets and resources, in order to significantly improve the efficiency of logistic activities. Also, the PI-enabled information sharing plays a vital role in the intelligent planning, coordination and control of logistics services (Kong et al, 2018). As a result, PI can be seen as an important way to achieve the goals of sustainable development, especially in reducing its environmental footprint (Lafkihi et al, 2019).…”
Section: Physical Internetmentioning
confidence: 99%
“…By promoting the creation of delivery channels (Luo et al, 2021), PI aims to reduce the fragmentation of logistics services by sharing logistics assets and resources, in order to significantly improve the efficiency of logistic activities. Also, the PI-enabled information sharing plays a vital role in the intelligent planning, coordination and control of logistics services (Kong et al, 2018). As a result, PI can be seen as an important way to achieve the goals of sustainable development, especially in reducing its environmental footprint (Lafkihi et al, 2019).…”
Section: Physical Internetmentioning
confidence: 99%
“…Lafkihi et al (2019) provided a literature review and future research opportunities in omnichannel E-commerce, and demonstrated that auction is a suitable mechanism for resource pricing problem. (Nadler and Kros, 2010;Kong et al, 2017;Kong, Huang, Luo and Yen, 2018) used auction mechanism to solve some problems in the supply chain and logistics. Zheng and Geroliminis (2016) proposed Stackelberg equilibrium which is investigated in a competitive behavior between different parking facility operators.…”
Section: Parking Policies and Parking Pricingmentioning
confidence: 99%
“…Place in IT-based marketing system is virtual. As reported by [44], the Internet can be used as the auction for the perishable product such as fish. The application of IT (e.g.…”
Section: Previous Studiesmentioning
confidence: 99%